Spatial distribution and morphometry of the Namibian coral mounds controlled by the hydrodynamic regime and outer-shelf topography - Tamborrino, Leonardo; Titschack, Jürgen; Wienberg, Claudia; Purkis, Sam; Eberli, Gregor P.; Hebbeln, Dierk (Frontiers in Marine Science, 2022)
Over millennial timescales, the proliferation of cold-water corals combined with sediment deposition within their frameworks are responsible of the formation of coral mounds. So far, these mounds have been mostly investigated as deep-sea biodiversity hotspots and geo-biological paleo-archives, whereas their morphological appearance has received much less attention. Here, we analysed the spatial distribution and the morphometry of the Namibian coral mounds to investigate the spatio-morphological development of early stage-coral mounds. As the Namibian mounds rarely exceed 20 m in height, key steps in the development of early-stage coral mounds (e.g. elongation, merging, limited gain in height compared to lateral extension) have been identified. With increasing size, coral mounds tend to be more elongated and downslope orientated. We interpret these data as result of the transition from an “inherited” to a “developed” morphology, thereby supporting an earlier hypothesis on the spatial development of coral mounds. This study reveals that the spatial-morphological appearance of coral mounds, often treated as a descriptive information, can provide valid information to understand their formation.